The international infant formula controversy: A dilemma in corporate social responsibility - Baker, James C. (Journal of business ethics, 1985)
One of the most controversial issues to face any industry has been the infant formula problem, especially in the less-developed countries (LDCs). Producers of infant formula were confronted with a boycott which evolved from a grass-roots level to one which involved many nations, international and national public agencies, non-profit organizations, scientific research institutions, large church denominations, and every company in the industry. An international boycott was aimed at Nestlé, one of the largest producers of infant formula., The aim of this paper is (1) to examine both sides of the controversy, and (2) to analyze the results of the boycott, specifically the introduction of product codes and changes in industry and company strategies. In both areas ethical implications were involved.